(3JJeI GdYed HbUjOI (B"(3HGMKkG Yf UfYg GdHQHGA(B"s
(3ChdgG (B:s
(3NP GdfMGS hKdKg ef Jadg hGdKdK ef eGA Mdja VjGA s
(3Vef eLehY , JQJjHgG (B: (3ef U (B11 - (3U(B31s
(3GdfSNI HgG MhGTs
(3GfXQ GdeLehYI Qbe (B91s
(3jdjgG ebWYGJ hbUGFO CNQi ai UfGYI GdcjejGA eQJHI bhGajgG Ydi MQha GdeYLes
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs